Association of social distancing and face mask use with risk of COVID-19 - Sohee Kwon (Nature Portfolio, 2021)
Estimating the effectiveness of COVID-19 control measures requires large prospective data including symptoms and personal risk factors. Here, the authors used data from smartphone-based application and found that individual face mask use was associated with a 64% reduced risk of COVID-19 symptoms.